2003
DOI: 10.1063/1.1594842
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the nanocrystals in oxyfluoride glass ceramics

Abstract: The crystallization of fluoro-silicate glasses obtained using high-purity SiO2, AlO1.5, CdF2, PbF2, ZnF2, and ErF3 has been investigated. Upon heat treatment, PbF2 nanocrystals form which host most of the Er3+ ions. The major peaks obtained by x-ray diffraction suggest that the nanocrystals are fluorite structured, but the low volume fraction of nanocrystals and line broadening due to their small size mean that unambiguous identification of the crystal structure is impossible. Therefore, atomistic simulation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 14 publications
0
38
0
Order By: Relevance
“…The unit cell parameter (a) of the crystallites can be obtained from the XRD results. We also calculated the Er 3+ concentration in the PbF 2 nanocrystals based on the F − interstitial compensation mechanism [14]. All calculated data are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The unit cell parameter (a) of the crystallites can be obtained from the XRD results. We also calculated the Er 3+ concentration in the PbF 2 nanocrystals based on the F − interstitial compensation mechanism [14]. All calculated data are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The first publication on oxyfluoride glass ceramics was by Wang 155 attributed this controversy to the low crystalline fraction and line broadening of the X-ray peaks due to the nanometric size of the crystals. They studied the glass composition 30SiO 2 is used in most of these devices, but a main drawback is the high phonon energy of the oxide host.…”
Section: Wang and Ohwaki's Compositionmentioning
confidence: 99%
“…4(a), it can be identified that the dendrite is ␤-PbF 2 . The content of RE ions in the ␤-PbF 2 can be determined by lattice parameter change as proposed by Beggiora et al [17]. Comparing the calculated lattice parameter (a = 0.589 nm) of RE ions modified ␤-PbF 2 with that (a = 0.594 nm) of pure ␤-PbF 2 , high concentration (∼7 mol%) of RE-ions in the ␤-PbF 2 crystals was determined if the difference of diameter between Er 3+ and Yb 3+ ions is ignored.…”
Section: The Relationship Between Microstructure and Up-conversion Prmentioning
confidence: 99%